Gearshift Control of a Dual Clutch Transmission Based on Sliding Mode Control for Nonlinear Uncertain Systems - Tran, Van Nhu (Old Journal, 2017)
The dual clutch transmission combines the advantages of the automatic transmission and performances, fuel efficiency of the manual transmission. In this system, the control of the dual clutch is a key point, especially when considering driving comfort. In this paper, we propose a control law for gearshift of a vehicle equipped with the dual clutch transmission based on sliding mode control for nonlinear uncertain systems. The goal is to ensure a rapid and smooth clutch engagement and avoiding engine no-stall. To achieve this goal, the clutch slipping speed and engine speed are controlled. In addition, uncertain parameters of the model and input disturbances are also considered. Several simulations are provided to show the effectiveness of proposed control law.